2011
DOI: 10.5603/fhc.2011.0071
|View full text |Cite
|
Sign up to set email alerts
|

The influence of caffeine on the biomechanical properties of bone tissue during pregnancy in a population of rats

Abstract: Abstract: Abstract: Abstract: The influence of pregnancy on bone tissue metabolism is not completely understood. Caffeine also has a potentially negative influence on bones. The aim of this study was the evaluation of changes in the bones of pregnant rats under the influence of caffeine. The experiment was carried out on Wistar rats. The evaluation of rats' bone tissue quality was performed based on bone density measurements and resistance examinations. It analyzed the impact of caffeine on the degree of bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 26 publications
2
29
1
Order By: Relevance
“…Caffeine intake is negatively associated with gestational changes in animals, such as lower rates of fertilization and embryonic implantation, low birth and placental weight, greater number of stillbirths, increased expression of apoptotic markers and altered placental and bone formation [9,27,[40][41][42][43][44][45][46] ( Table 1).…”
Section: Caffeine and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine intake is negatively associated with gestational changes in animals, such as lower rates of fertilization and embryonic implantation, low birth and placental weight, greater number of stillbirths, increased expression of apoptotic markers and altered placental and bone formation [9,27,[40][41][42][43][44][45][46] ( Table 1).…”
Section: Caffeine and Pregnancymentioning
confidence: 99%
“…Olchowik and colleagues [45] reported that 30 mg/day of caffeine intake during pregnancy had negative influence in female rats' bone tissue. Tomaszewski and colleagues [41], using X-ray microprobe to examine female rats fetuses treated with 30 mg/day of caffeine, observed that the decreased bone mineralization was dominant in the treated group.…”
Section: Caffeine Intake During Pregnancy: What Are the Real Evidences?mentioning
confidence: 99%
“…Since then, a number of studies have confirmed the negative effect of high doses of caffeine ingested during pregnancy both for the mother and the developing foetus [2,3,7,15,16,18,22,25,27,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine consumption has been associated with coronary heart disease, hypertension and adverse reproductive or developmental effects [7]. Olchowik et al [8] showed that caffeine intake during pregnancy (30 mg/day) had a negative influence on the bone tissue of female rats.…”
Section: Introductionmentioning
confidence: 99%